Объяснение:
в)
((5 3/7)`¹+(5 2/3)`²)•((-2,5)⁰+(-1)`¹)=
=((5 3/7)`¹+(5 2/3)`²)•(1+(-1))=
=((5 3/7)`¹+(5 2/3)`²)•0=0
а)
(а³)`²•(а`⁷)`¹ а`⁶•а⁷ а 1
—————— = ———— = —— = ——
(а`²)`² : (а`¹)⁴ а⁴ : а`⁴ а⁸ а⁷
б)
-2a `² a`² `¹
( ——— ) • ( ——— ) =
3b`³ 4b⁵
3b`³ ² 4b⁵ ¹
= ( ——— ) • ( ——— ) =
-2a a`²
9b`⁶ 4b⁵ 9b`¹ 9
= ——— • ——— = ———— = 9b`¹ = —
4a² a`² a⁰ b
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Объяснение:
в)
((5 3/7)`¹+(5 2/3)`²)•((-2,5)⁰+(-1)`¹)=
=((5 3/7)`¹+(5 2/3)`²)•(1+(-1))=
=((5 3/7)`¹+(5 2/3)`²)•0=0
а)
(а³)`²•(а`⁷)`¹ а`⁶•а⁷ а 1
—————— = ———— = —— = ——
(а`²)`² : (а`¹)⁴ а⁴ : а`⁴ а⁸ а⁷
б)
-2a `² a`² `¹
( ——— ) • ( ——— ) =
3b`³ 4b⁵
3b`³ ² 4b⁵ ¹
= ( ——— ) • ( ——— ) =
-2a a`²
9b`⁶ 4b⁵ 9b`¹ 9
= ——— • ——— = ———— = 9b`¹ = —
4a² a`² a⁰ b